2009
DOI: 10.3200/jach.58.1.83-90
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Well-Being and Suicidal Ideation Among College Students

Abstract: This investigation highlighted existential well-being as an important factor associated with lower levels of suicidal ideation among college students. Findings from this study focusing on the association between spiritual well-being and suicidality may prove especially beneficial to suicide prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 30 publications
8
64
2
4
Order By: Relevance
“…In a 5-year follow-up study of repeaters of suicidal attempts, it was reported that high anxiety, severe depression, psychiatric symptoms and young females with low education were significantly associated with repetition of attempted suicide [12]. Similarly, the identified protective factors against suicide and self-injurious behaviour are numerous, including treatment of underlying mental disorders, alcohol and drug abuse, physical disorders and others [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In a 5-year follow-up study of repeaters of suicidal attempts, it was reported that high anxiety, severe depression, psychiatric symptoms and young females with low education were significantly associated with repetition of attempted suicide [12]. Similarly, the identified protective factors against suicide and self-injurious behaviour are numerous, including treatment of underlying mental disorders, alcohol and drug abuse, physical disorders and others [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Death severs people from the realization of their dreams, leading to death anxiety. University students experience the severance of relationships through the death of parents or friends; it is then that they perceive the problem of their own life and death, and when they take control over their lives and obtain savoir-vivre [2]. Death anxiety is increased in students with little experience of death because their values are not established.…”
Section: Discussionmentioning
confidence: 99%
“…Those who are spiritually well can find meaning and goals in life in their current surroundings as well as future meaning and their ultimate goals. They show a positive attitude even in negative circumstances or environments, and can accelerate inner healing and peace by improving and revitalizing their inner defense abilities [1,2]. Accordingly, implementing a spiritual education or consultation program aimed at increasing university students' spiritual wellbeing may help them achieve the tasks they face and live healthy lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 With regard to religion, in general, religiosity has been found to be protective in terms of mental health (Wong, Rew & Slaikeu, 2006), with lower levels of depression in adolescents (Cotton, Larkin, Hoopes, Cromer & Rosenthal, 2005), and young adults (Taliaferro, Rienzo, Pigg, Miller & Dodd, 2009), and lower rates of suicidality in adolescents (Rew, Thomas, Horner, Resnick & Beuhring, 2001) and young adults (Taliaferro, Rienzo, Pigg, Miller & Dodd, 2009). However, there are strong connections between religiosity and negative views of homosexuality (Rowatt, LaBouff, Johnson, Froese & Tsang, 2009), and higher rates of internalised homophobia (Barnes & Meyer, 2012;Kralovec, Fartacek, Fartacek & Plöderl, 2014;Shilo & Savaya, 2012), and internalised homophobia is associated with poor mental health outcomes (Kralovec et al, 2014;Shilo et al, 2012).…”
Section: The Complexities Of Biblical Translation: Why the 'Average Jmentioning
confidence: 99%